Systematic Review : Effectiveness Health Behavior Intervention For Hypertension Prevention - FARIDA, BUNGA; febi, Febitya Valent Difiana; Rachmat , Rachmat Roebidin (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Hypertension is non communicable disease that a very common and serious condition that can lead to or complicate many health problems, People with hypertensions must controlled the symptoms of high pressure, when they forget to take a medicine it will increased risks of coronary and cerebrovascular events.This systematic review aim to describe the effectiveness health behavior intervention for hypertentions preventions behavior among patients. A systematic literature search was carried out on PubMed , PloS, Sagepub, Sciencedirect and Google Scholar to identify studies reported in English which were published in the last five years. Based on 19 studies that have been analyzed , Health Belief Model is a reliable and widely applicable framework for guiding behavioral change in hypertension prevention and control in hypertension prevention. This review present the effectiveness of health belief model in changing the hypertensions patients behavior, and improve their knowledge about hypertensions and its consequences.